Predicting Welding Deformation of Exposed Forged-and-welded Gear by the Integrated Computational Approach - Qu Tie; Xin Wen; Luo Wenze; Wang Chongyang; Hu Long; Huang Zhiquan; Deng Dean (Jixie chuandong)
In the current study, a large exposed forged-and-welded gear with a diameter of 7 160 mm is taken as the research object. An integrated computational approach is employed to predict the total welding deformation of the gear during welding process. Based on software MSC. Marc, three typical welded joints are extracted from the large forged-and-welded gear structures, and the inherent deformations of each joint under multi-pass welding conditions, are calculated by the thermo-elastic-plastic finite element method. The inherent deformations of each welded joint are converted into the corresponding inherent strains, and the total welding deformation of the welded gear is calculated using the elastic finite element method based on inherent strain theory. The numerical simulation results show that the radial shrinkage of the large forged-and-welded gear is about 11 mm after welding, and the amount of contraction in the circumference direction is about 3 mm.